Genetic identification informs on the distributions of vagrant Royal (Eudyptes schlegeli) and Macaroni (Eudyptes chrysolophus) Penguins - Shepherd, Lara; Miskelly, Colin; Cherel, Yves; Tennyson, Alan (Polar Biology, 2021)
International audience Understanding the movements of animals that spend much of their life at sea is difficult but important for effective conservation. Determining the at-sea distributions of Macaroni (Eudyptes chrysolophus) and Royal (Eudyptes schlegeli) Penguins poses particular challenges, including their occurrence in remote locations and difficulties in species identification owing to overlap in morphological characters, particularly in immature birds. Here we use DNA sequencing to examine vagrant Macaroni and Royal Penguins from Antarctica and New Zealand in order to improve understanding of their non-breeding distributions. Our sampling included samples from living birds, museum specimens and scavenged penguin remains recovered from the stomachs of Antarctic toothfish (Dissostichus mawsoni) caught north of the Ross Sea. Mitochondrial control region (HVRI) sequences indicated that the two samples from New Zealand were likely Royal Penguins as were the scavenged penguins. Both Macaroni and Royal Penguins were detected at Terre Adélie, Antarctica, despite the nearest breeding colony of Macaroni Penguins being 4000 km away. We provide the first evidence of Royal Penguins reaching the Ross Dependency. All but one of the vagrants were immature birds, supporting suggestions that this age group is the most likely to disperse large distances from the breeding colonies. Our study demonstrates how DNA sequences can assist in identifying taxa with similar or overlapping morphologies, as well as fragmentary bird remains.